The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1177/1069397110394310
|View full text |Cite
|
Sign up to set email alerts
|

What Observation Studies Can Tell Us About Single Child Play Patterns, Gender, and Changes in Chinese Society

Abstract: Our study focused on Chinese children’s play patterns in two different Chinese capitals: Chengdu—the capital of Sichuan in southwest China and Hohhot—the capital of the autonomous Inner Mongolia region in northern China. Unlike child psychologists working in China, who prefer survey instruments organized around parent and teacher interviews, the authors relied primarily upon behavioral observations. Their study is based on naturalistic observations of children in different age cohorts interacting in a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As age increased, boys were less likely to tattle on others, but they were also more likely than girls to become the targets of tattling. Our study therefore reveals a more complex picture of sex differences in aggression than prior observational or self-report studies on Chinese children 48 , 58 . Girls’ tactics are especially interesting: Tattling can help mitigate conflicts while asserting oneself, through seeking help from external authority.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…As age increased, boys were less likely to tattle on others, but they were also more likely than girls to become the targets of tattling. Our study therefore reveals a more complex picture of sex differences in aggression than prior observational or self-report studies on Chinese children 48 , 58 . Girls’ tactics are especially interesting: Tattling can help mitigate conflicts while asserting oneself, through seeking help from external authority.…”
Section: Discussionmentioning
confidence: 66%
“…Mainstream anthropology scholarship, including the Wolfs’ own works 45 , 50 , emphasized gender socialization ideology in Chinese culture, i.e., girls submitting to boys, rather than actual experience in childhood, therefore assumed a passive role of girls. Aligned with that gender ideology, the scant observational research of contemporary urban Chinese children found that boys displayed more dominance than girls 48 . This contrast might have resulted from differences in study design, that our data are based on a much more extensive fieldwork with a larger sample size, or that our study employed a more rigorous and sophisticated statistical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As age increased, boys were less likely to tattle on others, but they were also more likely than girls to become the targets of tattling. Our study therefore reveals a more complex picture of sex differences in aggression than prior observational or self-report studies on Chinese children 54,55 . Girls' tactics are especially interesting: Scolding and tattling can help mitigate conflicts while asserting oneself, with the former invoking one's own authority and the latter seeking external authority.…”
Section: Discussionmentioning
confidence: 67%
“…One important question is why Child Interview data did not show significant influences of age and gender on peer aggression. Gender and age differences in children's aggressive acts have been found in observational research on Han children in contemporary China (Jankowiak, Joiner, and Khatib 2011) as well as other cultures, such as those studied in SCS (Whiting and Edwards 1973) and its extension (Whiting and Edwards 1988). According to Margery Wolf (1978), gender and age were important factors in parental discipline in this community: local people saw ages 6 and 7 (about the median age of this Child Interview sample), when parental discipline becomes stricter, as a time of abrupt change, with parents clearly favoring boys over girls.…”
Section: Jing Xumentioning
confidence: 95%